A Neurologic Examination for Anesthesiologists: Assessing Arousal Level during Induction, Maintenance, and Emergence. (March 2019) - Reshef, Edith R.; Schiff, Nicholas D.; Brown, Emery N.
Abstract : Anesthetics have profound effects on the brain and central nervous system. Vital signs, along with the electroencephalogram and electroencephalogram-based indices, are commonly used to assess the brain states of patients receiving general anesthesia and sedation. Important information about the patient's arousal state during general anesthesia can also be obtained through use of the neurologic examination. This article reviews the main components of the neurologic examination focusing primarily on the brainstem examination. It details the components of the brainstem examination that are most relevant for patient management during induction, maintenance, and emergence from general anesthesia. The examination is easy to apply and provides important complementary information about the patient's arousal level that cannot be discerned from vital signs and electroencephalogram measures. Abstract : This article reviews the principal components of the neurologic examination that are most relevant to anesthesiologists for inferring a patient's level of brainstem function and arousal during induction, maintenance, and emergence from general anesthesia. The neurologic examination provides information about a patient's arousal level that is complementary to that provided by vital signs and electroencephalogram measures.